Analisis interaksi antara paparan asap rokok dan gizi dalam kejadian stunting di Indonesia: A literature review - Triswati, Triswati; Aji, Budi; Suratman, Suratman (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Stunting is a global health problem rooted in various factors, including poor nutrition and unhealthy household environments, one of which is exposure to cigarette smoke. This condition affects child growth, reduces immunity, and impacts future productivity. Purpose: To analyze the interaction between cigarette smoke exposure and nutrition on the incidence of stunting. Method: Literature review research followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were retrieved from Scopus, PubMed, Google Scholar, ResearchGate, and the Directory of Open Access Journals (DOAJ). After screening and evaluation, eight articles met the inclusion criteria. Results: Results: Exposure to household cigarette smoke and poor nutrition synergistically increase the risk of stunting in children. Cigarette smoke impairs nutrient absorption and the immune system, while poor nutrition exacerbates these effects. Conclusion: Stunting prevention requires a combination of adequate nutritional interventions and smoking control in the family environment. Keywords: Children; Cigarette Smoke; Nutrition; Family; Stunting. Pendahuluan: Stunting merupakan masalah kesehatan global yang berakar pada berbagai faktor, termasuk gizi buruk dan lingkungan rumah tangga yang tidak sehat, salah satunya paparan asap rokok. Kondisi ini berdampak pada pertumbuhan anak, menurunkan daya tahan tubuh, serta memengaruhi produktivitas di masa depan.Tujuan: Untuk menganalisis interaksi antara paparan asap rokok dan gizi dalam kejadian stunting di Indonesia.Metode: Penelitian literature review ini mengikuti pedoman PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Artikel diperoleh dari Google Scholar, Science Direct, PubMed, dan Directory of Open Access Journals (DOAJ). Setelah melalui proses penyaringan dan evaluasi, delapan artikel memenuhi kriteria inklusi.Hasil: Paparan asap rokok dalam rumah tangga dan gizi buruk secara sinergis meningkatkan risiko stunting pada anak. Asap rokok mengganggu penyerapan nutrisi dan sistem imun, sedangkan gizi buruk memperparah dampaknya.Simpulan: Pencegahan stunting perlu dilakukan melalui kombinasi intervensi gizi yang memadai dan pengendalian perilaku merokok di lingkungan keluarga. Kata Kunci: Anak; Asap Rokok; Gizi; Keluarga; Stunting.